Recent Advances in Molecular Image-Guided Cancer Radionuclide Therapy - Gao, Duo; Sun, Xianlei; Gao, Liquan; Liu, Zhaofei (Current Drug Targets, 2015)
Cancer-targeted radionuclide therapy is a promising approach for the treatment of a wide variety of malignancies, especially those resistant to conventional therapies. However, to improve the use of targeted radionuclide therapy for the management of cancer patients, the in vivo behaviors, dosimetry, and efficacy of radiotherapeutic agents need to be well characterized and monitored. Molecular imaging, which is a powerful tool for the noninvasive characterization and quantification of biological processes in living subjects at the cellular and molecular levels, plays an important role in the guidance of cancer radionuclide therapy. In this review, we introduce the radiotherapeutics for cancertargeted therapy and summarize the most recent evidence supporting the use of molecular imaging to guide cancer radionuclide therapy.
Keywords: Image-guided therapy